2020
DOI: 10.1364/oe.400246
|View full text |Cite
|
Sign up to set email alerts
|

Six-level hybrid extraction/injection scheme terahertz quantum cascade laser with suppressed thermally activated carrier leakage

Abstract: This work presents a six-level scheme terahertz (THz) quantum cascade laser (QCL) design in which the resonant-phonon (RP) and the scattering-assisted (SA) injection/extraction are combined within a single Al0.15Ga0.85As/GaAs based structure. By utilizing extra excited states for hybrid extraction/injection channels, this design minimizes the appearance of an intermediate negative differential resistance (NDR) before the lasing threshold. The final negative differential resistance is observed up to 260K and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Second, since the coupling between injection level and upper laser level (ull) should not be too strong for THz QCL, [20] resonant tunneling injection is inefficient for populating the ull according to theoretical analysis, especially at elevated temperature, leading to a reduction of PI. [21,22] Moreover, thermally activated carrier leakage to the continuum level and the weak coupling between ull and extraction level have also been suggested to reduce the electron population at ull, [5,19] and therefore spoils the PI.…”
Section: Introductionmentioning
confidence: 99%
“…Second, since the coupling between injection level and upper laser level (ull) should not be too strong for THz QCL, [20] resonant tunneling injection is inefficient for populating the ull according to theoretical analysis, especially at elevated temperature, leading to a reduction of PI. [21,22] Moreover, thermally activated carrier leakage to the continuum level and the weak coupling between ull and extraction level have also been suggested to reduce the electron population at ull, [5,19] and therefore spoils the PI.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that THz QCL quantum structure designs are critical for the temperature performance of the devices [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and have made great efforts to explore different THz QCL quantum structure designs. Multiple quantum designs, such as the bound-to-continuum (BTC) design [6,11,17,18], resonantphonon (RP) design [19][20][21], scattering-assisted (SA) design [4,22], phonon-photon-phonon (3p) design [23][24][25], direct-phonon design [26,27], split-well direct-phonon design [28,29], extraction-controlled design [30,31], and hybrid extraction/injection design [32], have been experimentally demonstrated and exhibited good temperature performance at different frequencies of ~1. 3-5.4 THz [33].…”
Section: Introductionmentioning
confidence: 99%
“…Without a suitable radiative barrier and injection barrier in the quantum cascade period, sufficiently high positive optical gain and population inversion, which are prerequisites for lasing operation, can typically be achieved only in the so-called negative differential resistance (NDR) region [36]. When the design bias is in the NDR region, the inhomogeneous and oscillating electric field domains emerge in the AR, and the lasing operation is generally disrupted [32,37,38]. In previous theoretical research attempts, superlattice designs were employed, and simulation results show that the design bias may be attainable in a positive differential resistance (PDR) region, but the extremely diagonal transition in the design failed to achieve sufficient optical gain [38].…”
Section: Introductionmentioning
confidence: 99%